Barriers to effective implementation of the nursing process among emergency ward nurses at a tertiary hospital, Accra; a cross sectional survey - Yaa Adutwumwaa Owusu-Ansah; Joana Agyeman-Yeboah (Elsevier, 2022)
Background: The nursing process provides a systematic approach to assessing the health care of well or ill individuals. It offers nurses a unique opportunity to offer personalized care to patients. However, its implementation remains a challenge in Ghana. Methods: A cross-sectional survey was conducted among emergency ward nurses at a tertiary hospital in the Greater Accra region of Ghana. Overall, 150 participants were conveniently selected. Alpha level of significance was set at 0.05. Chi-square analysis was performed to find association between the variables of interest and implementation of the nursing process. Results: Educational qualification, rank of nurses and years of experience were not associated (p > 0.05) with any of the indicators of individual factors that hinder implementation of the nursing process. Except for the response to whether management recognizes nurses for applying the nursing process (p < 0.05). All other items on health system-related factors hindering the implementation of the nursing process were not associated with the educational qualification of the nurses. The rank of nurses was associated with their responses to the health system-related question on whether work overload affected the implementation of the nursing process (p < 0.05) and nurses having multiple function (p < 0.05). Years of experience was not related to any health system-related item. Educational qualification, rank and years of experiences were not related to knowledge of the nursing process. Conclusion: Nurses had relatively high knowledge of the nursing process. Health system-related factors such as logistics other than individual factors such as limited information from patients and tedious documentation of the nursing process are reported to hinder the nursing process in the study setting. It is recommended that nurse managers put in place policies, provide the required logistics as well as regular supervisory function to enhance the use of the nursing process.